HUBUNGAN PENGETAHUAN GIZI, UANG JAJAN DAN PENDAPATAN ORANG TUA DENGAN KEJADIAN OVERWEIGHT PADA SISWA KELAS 4 DAN 5 SDN 001 SUKAJADI PEKANBARU - Husanah, Een (PROGRAM STUDI DIII KEPERAWATAN UNIVERSITAS ABDURRAB PEKANBARU, 2016)
The prevalence of overweight and obesity in children continued to increased significantly throughout the world .In indonesia riskesdas according to 2007 national prevalence of overweight children aged 6-14 years in males 9.5 % and in women 6.4 % , this figure will almost same with estimated who amounting to 10 percent in children aged 5-17 years. The purpose of this research is to find relations their knowledge about nutrition , snack money and income tuadengan scene overweight people. The kind of research this is research quantitative with the design cross sectional .As for the population this study were students grade 4 and 5 sdn 001 sukajadi pekanbaru which consisted of 240 students , with the sample of the 51 students. Research conducted in analysis by using the chi squThe prevalence of overweight and obesity in children continued to increased significantly throughout the world .In indonesia riskesdas according to 2007 national prevalence of overweight children aged 6-14 years in males 9.5 % and in women 6.4 % , this figure will almost same with estimated who amounting to 10 percent in children aged 5-17 years. The purpose of this research is to find relations their knowledge about nutrition , snack money and income tuadengan scene overweight people. The kind of research this is research quantitative with the design cross sectional .As for the population this study were students grade 4 and 5 sdn 001 sukajadi pekanbaru which consisted of 240 students , with the sample of the 51 students. Research conducted in analysis by using the chi square with 95 % confidence and the  p value < 0,05 atau Î± 5%. The results of the study the majority of respondents have of knowledge of good about their knowledge about nutrition and snack money received above average 8000 , and the average family income 4.000.000. The analysis shows there was a correlation between their knowledge about nutrition children with the incident overweight ( p = 0,022 also in snack money and income parents with the genesis overweight ( p = 0,005 and p = 0.010 ). Need to do activities weighing weight in monitoring purposes growth and students actively participate in making wall magazine so fellow students can sharing obtain information on overweight are with 95 % confidence and the  p value < 0,05 atau Î± 5%. The results of the study the majority of respondents have of knowledge of good about their knowledge about nutrition and snack money received above average 8000 , and the average family income 4.000.000. The analysis shows there was a correlation between their knowledge about nutrition children with the incident overweight ( p = 0,022 also in snack money and income parents with the genesis overweight ( p = 0,005 and p = 0.010 ). Need to do activities weighing weight in monitoring purposes growth and students actively participate in making wall magazine so fellow students can sharing obtain information on overweight